Biomimetic design of gradient and hierarchical platform based on carbon nanotubes and porous carbon polyhedrons for strain sensors and beyond. (26th May 2023) - Zhao, Songfang; Liu, Lin; Liu, Yikun; Zhou, Yunlong; Xia, Meili; Zhang, Yongjing; Li, Yang; Cao, Duxia; Gao, Yongju; Lai, Yuekun
Abstract: Currently, stretchable strain-sensing platforms are highly desirable for the full-range and accurate detection of human motions. However, it is also a grand challenge to fabricate strain sensors with a large sensing range, high sensitivity, and low detection limit. Inspired by the gradient and hierarchical structures in bones, a high-performance and multifunctional sensing platform with a gradient component distribution was reported by selecting porous carbon polyhedrons (PCP), PCP- welding -carbon nanotubes (PCP- w -CNTs), and CNTs as the functional nanomaterials to construct a novel bone-mimicking gradient conductive network by a facile layer-by-layer assembly, and elastic poly(styrene- block -butadiene- block -styrene) as the periosteum-like coating to being attached to conductive networks. Benefiting from the gradient structure and junction welding by manipulating the vertical component distribution of conductive fillers and in situ deposition, the strain sensors could detect small and large deformations with an ultralow detection limit (∼0.01% strain), a large sensing region (∼660% strain), high sensitivity (∼5797.83), fast response/recovery time (∼180/180 ms), and excellent robustness (∼1000 stretch-release cycles). Moreover, the composites can sense liquids due to their different solubility parameters. Graphical abstract: Image 1 Highlights: Biomimetic gradient structures are designed by layer-by-layer assembly. Gradient structure endows the sensors with high stretchability, GF, and robustness. Biomimetic composites can sense liquids due to their different solubility parameters. Diverse applications of tactile sensors are demonstrated.